Methodology for assessing negative external effects in the ecological field - Filiptsov, Andrey M.; Lahun, Marina A. (Journal of the Belarusian State University. Economics, 2024)
The methodological basis for the regulation of negative external effects in the ecological field as a component of sustainable development of the economic system is studied. Approaches to the assessment of the environmental component of sustainable development and methods of assessing environmental and economic damage are generalised. The methodology of calculation of damage from environmental pollution by the source which is a producer of products and the model for selecting the optimal technology and output volume are proposed.
Keywords: external effects; sustainable development; ecological safety; environmental protection; Republic of Belarus